Hypofractionated vs. conventional radiation therapy for stage III non-small cell lung cancer treated without chemotherapy. (1st February 2020) - Iocolano, Michelle; Wild, Aaron T.; Hannum, Margaret; Zhang, Zhigang; Simone, Charles B.; Gelblum, Daphna; Wu, Abraham J.; Rimner, Andreas; Shepherd, Annemarie F.
Abstract: Background: Patients with unresectable locally advanced NSCLC who refuse or are not candidates for chemotherapy often receive radiation therapy (RT) alone. Hypofractionated RT (HFRT) regimens are becoming increasingly common. An analysis of the National Cancer Database (NCDB) was performed to evaluate the practice patterns and outcomes of HFRT vs. conventionally fractionated RT (CFRT) in patients with stage III NSCLC undergoing definitive RT alone. Material and methods: The NCDB was queried for all patients with stage III NSCLC diagnosed between 2004 and 2014 who received RT alone. CFRT was defined as patients treated to a total dose of 60–80 Gy in 1.8–2 Gy daily fractions. HFRT was defined as patients treated to a total dose of 50–80 Gy in 2.25–4 Gy fractions. Logistic regression, univariable and multivariable analyses (MVAs) for overall survival (OS) and propensity score matched analyses (PSMAs) were performed. Results: A total of 6490 patients were evaluated: 5378 received CFRT and 1112 received HFRT. Median CFRT dose was 66 Gy in 2 Gy fractions vs. 58.5 Gy in 2.5 Gy fractions for HFRT. HFRT was associated with older age, lower biological effective dose (BED10 ), academic facility type, higher T-stage and lower N-stage. On initial analysis, HFRT was associated with inferior OS (median 9.9 vs. 11.1 months, p <.001), but after adjusting for the imbalance in covariates such as age, BED10, T-stage and N-stage using PSMA, the difference in survival was no longer significant ( p =.1). Conclusions: In the appropriate clinical context, HFRT can be an option for patients with locally advanced NSCLC who are not candidates for chemotherapy or surgical resection. HFRT needs to be further studied in prospective trials to evaluate toxicity and tumor control.